Self-compassion in medical students: a pilot study of its association with professionalism pressure - Světlák, Miroslav; Daňhelová, Šárka; Kóša, Barbora; Slezáčková, Alena; Šumec, Rastislav (BMC medical education, 2021)
BACKGROUND: To be a "good doctor" and have "good medical practices" are apparent goals for both medical students and medical faculties. However, the associated implicit and explicit standards could be a source of distress in the form of pressure to achieve professionalism. Self-compassion has been identified as a transtherapeutic factor that plays a crucial role in developing and maintaining mental health. It seems to be an essential meta-skill to learn, especially for medical students who often perceive imperfection as failure. In this pilot study, we investigated the qualities that medical students attribute to the "good doctor" concept, how they perceive themselves compared to this concept, and whether any possible discrepancy between these two perspectives could be associated with self-compassion. METHODS: Altogether, 301 medical students participated in the study (mean age 22.3 ± 2.1; 71.8 % female). The discrepancy between concepts was measured by a semantic differential consisting of a list of 36 adjectives and antonyms that students repeatedly mentioned in courses in their responses to the question "What should a doctor be like?" Self-compassion was measured by the Self-Compassion Scale. RESULTS: The obtained results offer an insight into students' conceptualization of a "good doctor" and the hierarchy of given characteristics. Statistical analysis revealed significant associations between the discrepancy between the "ideal" doctor concept vs. actual self-perception and Self-Compassion Scale scores. The more students are compassionate to themselves, the lower the discrepancy. CONCLUSIONS: The current pilot study supports the hypothesis that student self-compassion could play some role in the degree of discrepancy between the ideal "good doctor" image and student self-concept. This result could support the importance of educational interventions developing self-compassion for medical students. The proposed discrepancy measurement could also be a tool for measuring the effect of well-being programs aimed at self-compassion in medical students.
Keywords: dospělí; Medical students; Female; Empathy; učení; Adult; mladý dospělý; ženské pohlaví; empatie; lidé; Pilot Projects; Self-compassion; Students, Medical; pilotní projekty; Learning; Professionalism; studenti lékařství; profesionalita; Male; Young Adult; Good medical practice; mužské pohlaví; Humans